Endoscopic sinusectomy: 'a rose by any other name'. A systematic review of different endoscopic procedures to treat pilonidal disease. (29th October 2022) - Milone, Marco; Gallo, Gaetano; Grossi, Ugo; Pelizzo, Patrizia; D'Amore, Anna; Manigrasso, Michele; Perinotti, Roberto; La Torre, Marco; De Palma, Giovanni Domenico; Basso, Luigi
Abstract: Aim: Pilonidal sinus or Pilonidal Disease (PD) is a relatively common, benign but challenging condition. Although commonly encountered in practice, its ideal treatment is controversial. One of the most validated treatments is video‐assisted surgery. In this context, very similar endoscopic techniques have been published under different names. The aim of this systematic review is to assess the differences among these proposed techniques and their outcomes. Methods: The Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines were followed during all stages of this systematic review. A systematic search of the English literature was performed on multiple databases from 1 January 2014 to 3 April 2022. The primary outcome measure was the IDEAL framework stage of innovation. The key secondary outcome measures were the adherence to the IDEAL reporting guidelines, the Blencowe framework and the core outcome set (COS) for studies evaluating the introduction and evaluation of novel surgical techniques, the qualitative assessment using appropriate tools, the procedural variations and outcomes of each technique. Results: A total of 38 articles were included reporting a very similar technique under eight different acronyms. The number of patients varied from 9 to 250. Mean follow‐up ranged from 1 to 60 months. There was only one published study of IDEAL 3. The majority (58%) were IDEAL 2a studies. Reporting of domains in the IDEAL reporting guidelines and Blencowe framework was poor, with most studies not reporting the component steps of procedures or efforts to standardize them. Half of COS domains were markedly underreported. The quality of the evidence was categorized as having a risk of bias from moderate to critical level in all nine comparative non‐randomized series. Postoperative complications occurred in 0%–6% of cases, including surgical site infection, poor or failed wound healing bleeding, granuloma, haematoma, and pain requiring intervention. The recurrence rate varied from 0% to 22%. Conclusion: The study demonstrates that reporting on technical aspects of interventions for PD is poor, thus warranting a better‐quality control of surgical techniques. It is advisable to group all endoscopic procedures under the umbrella term of 'endoscopic sinusectomy', thus embracing the two main principles of this technique, that is, video assistance and PD ablation.